Children of Depressed Parents: Mechanisms of Risk and Implications for Treatment. 2002
DOI: 10.1037/10449-006
|View full text |Cite
|
Sign up to set email alerts
|

Parental depression and offspring disorders: A developmental perspective.

Abstract: Parental influences on the behavior and development of offspring pose questions that are among the oldest and most intractable in the human sciences. Parental depression as an influence is a special case within this larger domain. The research questions and methods, as well as the level of research understanding, are similar in the diverse content areas of parent-offspring associations. Although some principles of transmission undoubtedly generalize across domains, it is likely, too, that biological and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
0
20
2
Order By: Relevance
“…As noted by Radke-Yarrow [37], studies of offspring's symptoms and parents' diagnoses have carved these sources of offspring impairments into separate entities. However, their separateness is meaningful only as a first step in seeking to understand transmission processes.…”
Section: Limitations and Conclusionmentioning
confidence: 98%
See 1 more Smart Citation
“…As noted by Radke-Yarrow [37], studies of offspring's symptoms and parents' diagnoses have carved these sources of offspring impairments into separate entities. However, their separateness is meaningful only as a first step in seeking to understand transmission processes.…”
Section: Limitations and Conclusionmentioning
confidence: 98%
“…However, their separateness is meaningful only as a first step in seeking to understand transmission processes. This study moves to the next step of integrating multiple contributors to offspring's well-being by examining the combinations of offspring depression and parental diagnosis that jointly affect significant areas of offspring functioning [37]. After considering the severity of offspring's current depression, parental depression status was no longer directly associated with offspring's impairment.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Parental mental health problems have long been known to convey risk to offspring for a number of negative outcomes including depression, anxiety, and behavioral problems (Radke-Yarrow and Klimes-Dougan 2002). Cross-sectional and longitudinal studies have found associations between adolescent suicidal behavior and a family history of suicidal behavior, parent–child discord, and family dysfunction (Brinkman-Sull et al 2000; Spirito et al 2003; Wagner 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the intergenerational transmission of depressive syndromes is attributable, in part, to disruptions in interactions between parents and youth associated with depressive symptomatology (Gotlib & Goodman, 1999; Radke-Yarrow & Klimes-Dougan, 2002). This is not to minimize the genetic and contextual risks (Goodman & Gotlib, 1999) that are shared by parent and child, or to ignore evidence that children with behavioral or emotional difficulties place a burden on parents that may contribute to their distress (Gartstein & Sheeber, 2004; Patterson, Chamberlain, & Reid, 1982).…”
mentioning
confidence: 99%